Features of the formation of professional competence of a future foreign language teacher through simulation games - Orynbayeva, U.K.; Kaliyeva, K.M.; Akhmetova, M.K.; Bekdualieva, A.K. (Buketov University, 2024)
In the article the importance of using the simulation-game method for the formation of professional competence of future foreign language teachers was emphasized and its effective developmental impact was described. The principles and methods of the simulation game that contribute to the professional growth of students were considered. The authors of the article emphasize the necessity of professional development of future foreign language teachers and reveal the potential of simulation tasks. It is noted that learning through simulation game allows to achieve two goals at the same time. In addition, the authors note that the use of simulation games gives the learning process an interesting and practically oriented character, contributes to the development of students' universal competencies such as cooperation and critical thinking, which increases their competitiveness in the labor market. In the article the authors describe in detail the main stages of the simulation game method and offer a number of optimal linguistic and content tasks for the development of professional competencies. Based on the above, the authors conclude that it is necessary to introduce the simulation game as an effective method of teaching foreign languages in higher education institutions when training future teachers. The purpose of this article is to analyze the potential of using imitation tasks to improve the effectiveness of foreign language teaching. The main objective of the article is to describe the rules and principles of the method of imitation games, as well as to formulate the didactic foundations for the use of such games in the training of future foreign language teachers. On the basis of the studied theoretical sources and their own experience of using imitation games, the authors offer a set of tasks for teaching a foreign language that meets the requirements of language teaching methodology.
Имитациялық ойындар арқылы болашақ шетел тілі мұғалімінің кәсіби құзыреттілігін қалыптастыру ерекшеліктері
Особенности формирования профессиональной компетенции будущего учителя иностранного языка посредством имитационных игр
Keywords: simulative games; future specialist; communicative competence; professional competence; pedagogical tasks; principles; foreign language teacher; educational environment